O surf como meio terapêutico em indivíduos com transtorno obsessivo compulsivo - Col, Maísa de (My University, 2020)
Obsessive Compulsive Disorder (OCD) affects around 3% of the world population. Due to its abstruse nature, with different degrees of symptoms, it ends up becoming an obstacle to the patient's quality of life. With the purpose of assisting in the search for the well-being of individuals, this research aimed to analyze the practice of surfing as an alternative therapeutic means, for the treatment of individuals who have pathology linked to obsessive compulsive disorder, as well as to identify other possibilities of therapeutic processes that already have applicability to the referred disorder, from an integrative bibliographic research. Theories about surfing as a therapeutic medium are innovative, but there are already beneficial results in the quality of life of the individuals who practice it. In order to solidify as an alternative therapy for the treatment of OCD, surfing practices will be necessary with a longer period of experience and a greater number of diagnosed individuals, leaving a possibility for further studies. [resumo fornecido pelo autor]
O Transtorno Obsessivo Compulsivo (TOC), acomete em torno de 3% da população mundial. Por sua abstrusa, com graus de sintomas diversos, acaba se tornando um empecilho para a qualidade de vida do paciente. Com o propósito de auxiliar na busca do bem-estar dos indivíduos, a presente pesquisa objetivou analisar a prática do surf como meio terapêutico alternativo, para o tratamento de indivíduos que apresentam patologia ligada ao transtorno obsessivo compulsivo, assim como identificar outras possibilidades de processos terapêuticos que já apresentam aplicabilidade ao referido transtorno, a partir de uma pesquisa bibliográfica integrativa. As teorias acerca do Surf como meio terapêutico são inovadoras, mas já há resultados benéficos na qualidade de vida dos indivíduos que o praticam. A fim de se solidificar como terapia alternativa para o tratamento do TOC, as práticas de Surf, serão necessárias com um maior período de vivências e maior número de indivíduos diagnosticados, ficando uma possibilidade para novos estudos. [resumo fornecido pelo autor]
Keywords: Transtorno obsessivo-compulsivo; Qualidade de vida; Surfe